Effect of acetaminophen on endurance cycling performance in trained triathletes in hot and humid conditions - Wijekulasuriya, G. A.; Coffey, V. G.; Badham, L.; O`Connor, F.; Sharma, A. P.; Cox, G. R. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The effect of acetaminophen (ACT, also known as paracetamol) on endurance performance in hot and humid conditions has been shown previously in recreationally active populations. The aim of this study was to determine the effect of ACT on physiological and perceptual variables during steady-state and time-trial cycling performance of trained triathletes in hot and humid conditions. Methods: In a randomized, double-blind crossover design, 11 triathletes completed ~60 minutes steady-state cycling at 63% peak power output followed by a time trial (7 kJ·kg body mass-1, ~30 min) in hot and humid conditions (~30°C, ~69% relative humidity) 60 minutes after consuming either 20 mg·kg body mass-1 ACT or a color-matched placebo. Time-trial completion time, gastrointestinal temperature, skin temperature, thermal sensation, thermal comfort, rating of perceived exertion, and fluid balance were recorded throughout each session. Results: There was no difference in performance in the ACT trial compared with placebo (P = .086, d = 0.57), nor were there differences in gastrointestinal and skin temperature, thermal sensation and comfort, or fluid balance between trials. Conclusion: In conclusion, there was no effect of ACT (20 mg·kg body mass-1) ingestion on physiology, perception, and performance of trained triathletes in hot and humid conditions, and existing precooling and percooling strategies appear to be more appropriate for endurance cycling performance in the heat.